2013
DOI: 10.3109/15412555.2012.727921
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in CT Phenotypes in COPD

Abstract: Background Whether African Americans (AA) are more susceptible to COPD than non-Hispanic Whites (NHW) and whether racial differences in disease phenotype exist is controversial. The objective is to determine racial differences in the extent of emphysema and airway remodeling in COPD. Methods First, 2,500 subjects enrolled in the COPDGene study were used to evaluate racial differences in quantitative CT (QCT) parameters of % emphysema, air trapping and airway wall thickness. Independent variables studied incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…In a previous analysis among the first 2500 subjects from the COPDGene study, Hansel and colleagues observed that AA subjects had less overall emphysema, as well as less lower lobe emphysema than NHW (23). We demonstrate that the sex-based differences in emphysema are less marked in AA subjects but the trend is still present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous analysis among the first 2500 subjects from the COPDGene study, Hansel and colleagues observed that AA subjects had less overall emphysema, as well as less lower lobe emphysema than NHW (23). We demonstrate that the sex-based differences in emphysema are less marked in AA subjects but the trend is still present.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these trends have not been fully explored among African American populations. One study among a subset of subjects from COPDGene demonstrated that AA had less overall emphysema than NHW (23). A further analysis of emphysema differences within these subgroups and across different races is an essential step towards understanding how COPD can develop and progress by sex, insights which may inform sex-specific clinical care of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the severity of emphysema differs among ethnic groups, even with similar lung function impairment. 25 The COPD patients with hereditary alpha-1 antitrypsin deficiency, who often manifest severe emphysema, are extremely rare in China. 26 Since we screened almost all AECOPD patients who visited our emergency department without selection, and the mortality was only a little lower than in other cohorts, 3,4,17 we consider that this cohort covered a wide range of GOLD categories and different degrees of emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar fashion, the role of asymptomatic viral infections may also have had important effects on a number of endpoints in studies of nasal remodeling (9). Finally, there may be genetically regulated differences in remodeling processes, related to race as well as other factors, as has been suggested in other airway diseases (10).…”
mentioning
confidence: 90%